Dynamics of endomarketing in the fast food restaurant FRISBY S.A.- Valentina Alzate - Natalia Sosa - Laura Gutierrez (GEON Journal (Management, Organizations and Business), 2015)
The research is conducted in the fast food restaurant FRISBY SA City Pereira during the year 2015 to meet the dynamics of endomarketing and brand building. It is intended for employees of restaurants FRISBY SA de Pereira qualitatively. The endomarketing has been studied for over 25 years; Berry is one of the major references and a pioneer of endomarketing; So in 1981 he was the first to call internal clients to employees. This approach arose from the need to improve people management and customer service. Empirical treatment stimulated different interpretations and conceptualizations on the subject; as a result different applications emerged in the form of development methodologies with some points in common as employee satisfaction and customer.The endomarketing, is a set of strategies that have begun to implement a large number of companies around the world. These strategies are intended to "sell" the company to the employees that form and make sense of belonging. Human resources are one of the largest bases for an organization and gaining a competitive advantage applied to one of the internal marketing models such as the model of Berry. In this dynamic, the importance of analyzing the management of resources is generated. Thus; Pereira, in fast food restaurant, FRISBY SA, evolution, development and marketing of the internal dynamics is analyzed.
Keywords: Internal marketing; Customer service; Organizational communication; Empowerment